2020
DOI: 10.1016/j.fm.2019.103287
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen sources preferences of non-Saccharomyces yeasts to sustain growth and fermentation under winemaking conditions

Abstract: Wine-related non-Saccharomyces yeasts are becoming more widely used in oenological practice for their ability to confer wine a more complex satisfying aroma, but their metabolism remains unknown. Our study explored the nitrogen utilisation profile of three popular non-Saccharomyces species, Torulaspora delbrueckii, Metschnikowia pulcherrima and Metschnikowia fructicola. The nitrogen source preferences to support growth and fermentation as well as the uptake order of different nitrogen sources during wine ferme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 38 publications
10
63
0
1
Order By: Relevance
“…As a general rule, the lag phase of sequential fermentation during which M. pulcherrima was the only yeast in the medium was shorter than that of S. cerevisiae pure culture. This result was consistent with previous findings indicating a shorter lag phase for M. pulcherrima (Su et al, 2020). The changes in the lag phase duration in response to changes in nutrient availability were similar for both strains.…”
Section: Nitrogen Consumption By M Pulcherrima Alters the Fermentatisupporting
confidence: 93%
See 1 more Smart Citation
“…As a general rule, the lag phase of sequential fermentation during which M. pulcherrima was the only yeast in the medium was shorter than that of S. cerevisiae pure culture. This result was consistent with previous findings indicating a shorter lag phase for M. pulcherrima (Su et al, 2020). The changes in the lag phase duration in response to changes in nutrient availability were similar for both strains.…”
Section: Nitrogen Consumption By M Pulcherrima Alters the Fermentatisupporting
confidence: 93%
“…In fact, when nitrogen was limiting (80 mg/L), the substantial consumption of nitrogen sources during the M. pulcherrima pure culture stage, up to 80% of the provided YAN, prevented the further implantation of S. cerevisiae, leading to a slow-down of fermentation. In the case of moderate and high initial YAN contents, the residual nitrogen level was higher at the time of S. cerevisiae addition, between 95 and 190 mg N/L, but some specific nitrogen sources, such as branched amino acids, glutamate and glutamine, were exhausted, in accordance with the sequence of the consumption of nitrogen sources by M. pulcherrima previously reported by Su et al (2020). As a consequence, the nitrogen resources available to promote further S. cerevisiae implantation were mainly composed of proline, tryptophan, glycine and alanine, which support the growth and fermentation of the yeast poorly (Godard et al, 2007;Fairbairn et al, 2017).…”
Section: Nitrogen Consumption By M Pulcherrima Alters the Fermentatisupporting
confidence: 86%
“…These results do not agree with Prior et al [33], who reported no difference in amino acids' uptake in L. thermotolerans or T. delbrueckii, with and without ammonium. Under this condition, the latest amino acid consumed by T. delbrueckii and L. thermotolerans was glycine, which has been previously described as a poor nitrogen source for several yeast species [12,32,35,56,57]. Indeed, glycine was also one of the less preferred amino acids for M. pulcherrima and S. bacillaris, being even excreted/produced by M. pulcherrima in SM-Mix.…”
Section: Discussionmentioning
confidence: 92%
“…While nitrogen consumption and preferences are well researched in S. cerevisiae [17,[23][24][25][26][27][28][29][30][31], nutrient uptake by non-Saccharomyces yeasts has not been extensively studied. Available studies have analyzed the preferential nitrogen sources of some non-Saccharomyces yeasts, focusing on their capacity to assimilate different nitrogen compounds, their rate of consumption, or their influence in aroma production [2,19,[32][33][34][35][36][37][38]. The firsts studies reported that the nitrogen sources directly affect the fermentation performance and yeast growth in a species-specific manner [32,39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation